2020
DOI: 10.1039/d0ra03892j
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic aspects of saccharide dehydration to furan derivatives for reaction media design

Abstract: The conversion of abundant hexoses and pentoses to 5-hydroxymethylfurfural (5-HMF) and 2-furfural (2-F) is subject to intensive research in the hope of achieving competitive production of diverse materials from renewable resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 124 publications
1
24
0
Order By: Relevance
“…[29][30][31]36 As known that the solvent also affected the dehydration process of fructose conspicuously through coordinating or activating intermediates. 7,[37][38][39][40] Hence, the effect of organic solvent with different structure on fructose dehydration with an aid of LiCl was investigated inevitably. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[29][30][31]36 As known that the solvent also affected the dehydration process of fructose conspicuously through coordinating or activating intermediates. 7,[37][38][39][40] Hence, the effect of organic solvent with different structure on fructose dehydration with an aid of LiCl was investigated inevitably. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…are the prevalent feedstocks due to their much easier dehydration process in the presence of acid catalysts. 6,7 So far, diverse catalysts involving strong mineral acids (HCl, H 2 SO 4 , H 3 PO 4 , etc. ), strong metal-based Lewis acids (Cr 3+ , Sn 4+ , Fe 3+ , etc.…”
Section: Introductionmentioning
confidence: 99%
“…Glucose produced a minor 10 % HMF yield while xylose produced a much higher furfural yield, 62 % (Table 1, entries 1–2). It is proposed that a higher reactivity of xylose compared to glucose could be connected to the less substituted C5 atom, which, according to a certain proposed mechanism, is responsible for the C2‐O attack on it (Blue path in Figure S1, Supporting Information) [33–35] . However, this mechanism does not have any consistent observations, and the most likely pathways, according to the literature, are the aldose isomerization to ketose either through hydride shift or through enediol intermediate (Green and red paths in Figure S1, respectively) [35] .…”
Section: Resultsmentioning
confidence: 98%
“…[33][34][35] However, this mechanism does not have any consistent observations, and the most likely pathways, according to the literature, are the aldose isomerization to ketose either through hydride shift or through enediol intermediate (Green and red paths in Figure S1, respectively). [35] Isomerization is often catalyzed by Lewis acids such as ZnCl 2 . [36] However, our experiments revealed that adding ZnCl 2 as a catalyst did not improve the HMF yield, and using fructose as feedstock increased the HMF yield only from 10 % to 17 % (Table 1, entries 4-5).…”
Section: Possible Hmf-des Interactionmentioning
confidence: 94%
“…HMF is a versatile intermediate in the production of value-added chemicals such as alternative fuels, diesel fuel additives, industrial solvents, bioderived polymers, etc. A typical strategy for the synthesis of HMF is the dehydration reaction of fructose/glucose using a variety of catalytic materials such as metal complexes and oxides, metal halides, ion-exchange resins, zeolites, functionalized carbonaceous materials, functionalized mesoporous materials, acidic ionic liquids (ILs) including organic inorganic acids, etc. The main drawback for some of these catalytic systems such as equipment corrosion and difficult product isolation, low product yield, longer reaction times in the case of solid acid catalysts, and the low thermal stability of the resin-based catalysts hampering reaction efficiency. Even though a handful of MOF-based catalysts for fructose to HMF production is available in the literature, the design and development of stable and efficient catalysts are in demand considering the industrial importance of HMF. MOFs with a highly porous and ordered nature with coordinatively unsaturated metal sites and an organic ligand component with inherent functional groups or the introduction of desired functional groups into MOFs through postsynthetic modification (PSM) can probably promote substrate transfer within the MOF catalyst in facilitating HMF production by an efficient catalytic reaction.…”
Section: Introductionmentioning
confidence: 99%